Unravelling the distinct surface interactions of modified graphene nanostructures with methylene blue dye through experimental and computational approaches - Manappadan, Zinoy; Kumar, Shubham; Joshi, Krati; Govindaraja, Thillai; Krishnamurty, Sailaja; Selvaraj, Kaliaperumal (Journal of Hazardous Materials, 2020)
Nanoscopic modifications leading to multi-dimensional graphene structures are known to significantly influence their candidature for several applications including catalysis, energy storage, molecular sensing and most significantly adsorption and remediation of harmful materials such as dyes. The present work attempts to identify the key trajectories that connect the structural qualification with a chosen application, viz., the interactive forces in dye remediation. Various physico-chemically Modified Graphene Nanostructures (MGNs) such as 2 dimensional Graphite, Graphene Oxide (GO), reduced GO (rGO), holey rGO, and 3 dimensional GO hydrogel and Holey GO hydrogel are chosen and synthesised herein. These represent varieties of physicochemical features with respect to their dimensionality, surface features such as oxygen functionality, nanoscopic holes etc., that contribute to their characteristic overall surface interactions. Methylene Blue (MB), a popular industrial effluent posing major environmental concern is chosen to be a probe adsorbate in this case study. An exclusive real time in-situ UV visible spectral experiment provides the revealing reasons behind the outstanding performance of 2D GO sheets with an adsorption capacity of greater than 92 % even at high MB concentrations (>2000 ppm). A complex dependency of various factors such as surface oxygen, morphology, nanoporosity etc. on the unique overall interaction with an adsorbent such as MB by all these adsorbates is demonstrated using experimental and DFT based computational studies. Electrostatics and hydrogen bonding are understood to be the two dominant forces driving the MB adsorption on the best performing GO here.
Keywords: Density functional theory; In-situ UV-vis spectroscopy; Interactions; Methylene blue; Modified Graphene Nanostructures